The Effect of Product Quality, Perceived Value, and Brand Image on Customer Loyalty Through Customer Satisfaction as A Mediating Variable in Onda Brand in Surabaya - Kiki Puput Puspitasari; Tri Andjarwati; Ulfi Pristiana (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze: (1) the effect of product quality, perceived value, and brand image on customer satisfaction; (2) the direct effect of product quality, perceived value, and brand image on customer loyalty; (3) the effect of customer satisfaction on customer loyalty; and (4) the mediating role of customer satisfaction in the relationships between the three independent variables and customer loyalty. Research is grounded in Expectation-Disconfirmation Theory (EDT) and the Stimulus-Organism-Response (S-O-R) theory. The research employs a quantitative approach with an explanatory research design. The sample consists of 475 respondents who are ONDA customers in Surabaya, selected using purposive sampling. Data were collected through questionnaires and analyzed using Partial Least Squares (PLS) with SmartPLS. The findings reveal that: (1) product quality, perceived value, and brand image each have a positive and significant effect on customer satisfaction; (2) product quality, perceived value, brand image, and customer satisfaction each have a positive and significant direct effect on customer loyalty; and (3) customer satisfaction partially mediates the effects of product quality, perceived value, and brand image on customer loyalty.